PENGGUNAAN VIRTUAL REALITY PADA GAME CREED : RISE TO GLORY-CHAMPIONS EDITION DI GAME BLINK PADANG - Tasya Chayrina; Awalia Rahmatia, Adek Kurniawan, Nabila Aprilioni, Vidya Nofriza, Chelsy Putri, Rini Novita (ADISAM PUBLISHER, 2024)
The development of Virtual Reality (VR) technology has changed the paradigm in the entertainment industry, especially in the context of games. This research explores the use of VR in the game